Regulatory performance of the bureau of public enterprises in Nigeria : a study of the telecomunications sector (2002-2012) - Salawu, Ibrahim Ogirima (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
Nigeria is one of the countries that has been caught by the global wave of adopting policy of privatisation as a form of statecraft. This is primarily meant to transfer state-owned enterprises into private hands. Arguments advanced on the inherent ability of privatisation to boost efficiency and equally reduce waste that characterized state management of enterprises. The need to ensure a credible, transparent and professional handling of such a process necessitates the establishment of the Bureau of Public Enterprises (BPE). Complaints of non- performance of about 80% of enterprises privatized by the BPE, necessitate a probe into the implementation machinery put in place to handle this sensitive national objective. This is with a view to affirm a hypothesized framework premised on the assumption that the challenge of autonomy and capacity faced by the BPE, explains the poor performance enunciated by the federal government of Nigeria. The telecommunications sector, which is one of several sectors in which the BPE has operated for over a decade, is used as a benchmark for a focused and in-depth study. The study assumes that government's criticism of the BPE for non-performance would not be objectively evaluated without a probe into the level of independence and technical know-how of the implementing architecture for privatization. This is achieved by using the broad assumption in Guislain (1997) thesis of autonomy and capacity. To enhance the measurability of these as related to performance of the BPE, Rockart and Christines (1981) Critical Success Factor theory which provides a more detailed breakdown of items to be measured under the triad is subsumed into Guislain's thesis. It is on this framework that the study builds its affirmation of relationship amongst the variables using Spearman's correlation coefficient. The study triangulates its (quantitative and qualitative) findings, having generated primary data from the Directorate cadre of the BPE and other key stakeholders in the telecommunications sector privatization. Statistical Packages for Social Sciences (SPSS) version 20.0 was used in processing and managing data for this study. Findings from this study indicate that the BPE possesses the requisite Autonomy and Capacity for Performance. However, the study reveals that capacity as a mediating/intervening variable should be consciously increased for performance of the BPE, as autonomy on its own does not guarantee performance as reflected in the telecommunications sector reform in Nigeria.